Seronegative spondyloarthropathy-related sacroiliitis: Differencial diagnosis between infectious sacroiliitis and spondyloarthritis, where the inflammation in the sacroiliac joint starts - Dejan Spasovski (Archives of Clinical Nephrology - Peertechz Publications, 2020)
Introduction: Very often late diagnosis in spondylitis ankylosans (SA) in the period between 5 to 10 years is due to unstandardized diagnostic method besides established diagnostic criteria. But, they are very restrictive and not practical for early diagnosis of SA, because are based on proved radiographic changes. Aim: Sacroiliitis (SI) as a sole entity rarely exists, usually is a part of a diagnostic mosaic of SA and related spondyloarthropathies (SpA). Surely proved SI clinically and radiographically means sure diagnosis of SA, especially in the early stage of the disease. Material and methods: Highly selective group of patients with SA was followed in the period of one year: group of 23 patients (pts) with unconvincing radiographic changes for SA from 1-2° and group of 21 pts without radiographic changes i.e. 0°. Beside SA, both groups fulfilled at least another from the listed conditions: 1.oligoarthritis; 2. enthesitis; 3. iridocyclitis; 4. positive family history for SA; 5. positive antigen HLA-B27 and 6. Elevated ESR > 30mm/h. Results: After observational period of one year in the group A 11/21 pts were with SA. In the group B only 6/23 pts were with SA; the others were transformed in different directions: 4/23 in the group of spondyloarthropathies (SpA) - 2 pts with Psoriatic spondyloarthropathy (PsSpA), 1 patient with Reiter syndrome (RS)and 1 patient with Entericspondyloarthropathy (ESpA). The others 8/22 pts were still undefined SpA. Conclusion: Our results showed that defining of SA was crucial in the diagnosis of SA. The fact that most of cases with authentic SA were in group A with minimal radiographic changes from 1-2° in comparison with group B without radiographic changes showed the necessity of using other imaging techniques (scan, MRI) for earlier detection of SI in the so called pre-radiographic stage which lasts 2-4 years, when radiographic findings are absent. Clinical (symptomatic) SI without radiographic changes according to the findings of pts in the group B gives a possibility for overlap to other entities in the group of SpA.